Socioeconomic inequality in stage at diagnosis of nasopharyngeal carcinoma: a cross-sectional study - Joko Mulyanto; Anton Budhi Darmawan; Anisa Kapti (Oto Rhino Laryngologica Indonesiana, 2016)
Background: Nasopharyngeal carcinoma (NPC) is head and neck cancer with the highest incidencein Indonesia, and leads Indonesia as one of the countries with the highest incidence of NPC in the world.Early diagnosis is an important prognostic factor in NPC management. However, most of the NPC patientswere diagnosed at the advanced stage. Delayed diagnosis is contributed by several factors includingsocioeconomic status.Objective: To find out the association between socioeconomic status with stageat diagnosis of NPC patients in Indonesia.Methods: A cross-sectional study was conducted and 57 NPCpatients were consecutively recruited from ENT clinic Margono Soekarjo Hospital as study subjects.Socioeconomic status was measured by income level, educational level, employment status, and healthinsurance coverage. Stages at diagnosis were categorized into early and advanced stage based on theclinical stage. Degree of socioeconomic inequality was analyzed by logistic regression.Results: Incomelevel below poverty line (OR 5.39; 95% CI: 1.36-22.42), basic educational level (OR=3.81; 95% CI:1.11–13.09), currently employed (OR=3.59; 95% CI: 1.07–12.00) had higher probability to be diagnosedat advanced stage. After multivariate analysis, only employment status (OR=5.74; 95% CI: 1.25 – 26.21)contributed significantly to probability of being diagnosed at advanced stage.Conclusion: Socioeconomicstatus was associated with stage diagnosis of NPC levels. Socioeconomic inequality in stage at diagnosisof NPC patients did exist in Indonesia, and employment status was the most contributing factor. Keywords: Socioeconomic status, inequality, stage at diagnosis, nasopharyngeal carcinoma ABSTRAKLatar belakang: Karsinoma nasofaring (KNF) merupakan keganasan kepala leher dengan insidenstertinggi di Indonesia, dan menyebabkan Indonesia menjadi salah satu negara dengan insidens KNFtertinggi di dunia. Diagnosis dini merupakan salah satu faktor prognostik penting dalam penatalaksanaanKNF. Meskipun demikian, sebagian besar pasien KNF didiagnosis pada stadium lanjut. Diagnosisterlambat dipengaruhi oleh berbagai faktor, antara lain status sosial ekonomi. Tujuan: Mengetahuihubungan antara kesenjangan sosial ekonomi dengan stadium diagnosis pasien KNF di Indonesia. Metode:Desain penelitian adalah studi potong lintang, dengan 57 subjek penelitian diambil secara konsekutifdari klinik THT RS Margono Soekarjo. Status sosial ekonomi diukur melalui tingkat penghasilan, tingkatpendidikan, status pekerjaan, dan cakupan asuransi kesehatan. Stadium diagnosis diukur berdasarkanstadium klinis, dan dikategorikan menjadi stadium awal dan stadium lanjut. Tingkat kesenjangan sosialekonomi dianalisis menggunakan regresi logistik. Hasil: Tingkat penghasilan di bawah garis kemiskinan(OR=5,39, CI 95%: 1,31–22.42), tingkat pendidikan dasar (OR=3,81, CI 95%: 1,11–13,09), sedangbekerja (OR=3,59, CI 95%: 1,07–12,00), mempunyai peluang lebih tinggi untuk didiagnosis pada stadiumlanjut. Hasil analisis multivariate menunjukkan hanya status pekerjaan (OR=5,74, CI 95%: 1,25–26,21)yang secara bermakna meningkatkan peluang didiagnosis pada stadium lanjut. Kesimpulan: Status sosialekonomi berhubungan dengan stadium diagnosis pasien KNF di Indonesia. Terdapat kesenjangan sosialekonomi pada stadium diagnosis pasien KNF di Indonesia, dan status pekerjaan merupakan faktor yangmemberikan kontribusi terbesar.  Kata kunci: Status sosial ekonomi, kesenjangan, stadium diagnosis, karsinoma nasofaring Author Correspondence: Joko Mulyanto, Department of Public Health and Community MedicineFakultas Kedokteran Universitas Jenderal Soedirman. Email: jkmulyanto@gmail.com.